Analisis Determinan Kinerja Keuangan BPR di Kota dan Kabupaten Tegal Tahun 2016-2020 - Monalisa; Hapsari, Ira Maya (Major Management, Faculty of Economics and Business, Universitas Pancasakti Tegal, 2021)
The aims of this research are 1). to find out and obtain empirical evidence of the effect of BOPO on financial performance. 2). To find out and get empirical evidence of the effect of LDR on financial performance. 3). To find out and get empirical evidence of the effect of NPL on financial performance. 4). To find out and get empirical evidence of the effect of CAR on financial performance. 5). To find out and get empirical evidence of the effect of cash ratio on financial performance. 6). To find out and obtain empirical evidence of the effect of BOPO, LDR, NPL, CAR, and cash ratio together on financial performance. The research method used in this study is a descriptive method using a quantitative approach. The data collection technique that the author uses in this research is documentation. While the data analysis method used is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, partial hypothesis testing, simultaneous hypothesis testing, and coefficient of determination. The results of this study are 1) There is an effect of BOPO on the financial performance of BPRs in the City and Regency of Tegal in 2016-2020. 2). There is no influence of LDR on the financial performance of BPR in the City and Regency of Tegal in 2016-2020. 3). There is no effect of NPL on the financial performance of BPR in the City and Regency of Tegal in 2016-2020. 4). There is an effect of CAR on the financial performance of BPR in the City and Regency of Tegal in 2016-2020. 5). There is no effect of the cash ratio on the financial performance of BPRs in the City and Regency of Tegal in 2016-2020. 6). There is a joint effect of BOPO, LDR, NPL, CAR, and cash ratio on the financial performance of BPRs in the City and Regency of Tegal in 2016-2020.